Atmospheric diffusion model for Delhi for regulatory purposes - GUPTA, R. N.; PADMANABHAMURTY, B. (MAUSAM, 1984)
To assess the air quality over short periods of the order of an hour to a day of relatively stable pollutants over an urban area, a model has been developed. The steady state Gaussian diffusion equations for point sources and their integration for area sources have been utilised. The maximum concentrations pf sulphur dioxide averaged over 24 hours by this model during any of the four seasons at Delhi due to area and point sources, has not exceeded United States Environmental Protection Agency’s (US EPA) Primary Air Quality. Standards. However, in some pockets in Delhi around Industrial areas, 24-how. maximum concentration exceeded US EPA secondary standards.